Innowacyjność przedsiębiorstw przetwórstwa przemysłowego w województwie warmińsko-mazurskim - Grzybowska, Barbara (Innovativeness of Industrial Processing Enterprises in Warmia and Mazury Province, 2006)
In the article one presented general tendencies in area of industrial enterprises innovativeness in province of Warmia and Mazury. The enterprises were divided according to level of technics. Expenditures on innovative activity and sales value of new and improved products were measures of innovativeness. The analysis shows that the economy in region is dominated by low technology firms. These enterprises spent 71% expenditures on innovation among all enterprises in region. Sales value of new and improved products achieved 40% of sales value of all innovative products in province.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 74-81